Penerapan Algoritma First In First Out Pada Sistem Informasi Manajemen di Hade Laundry - Liliosa Julpartin, Yuliana; Kurniawan, Hendra (Universitas Islam Balitar, 2024)
Utilization of information technology can encourage business activities in a better direction, including the laundry business. This business is growing very rapidly in densely populated areas, especially in big cities. This was triggered by changes in people's lifestyles and busy lives, making laundry services a practical solution. Hade laundry is a business unit that concentrates on laundry services in the city of Makassar. This business unit still uses manual recording, so it is very vulnerable to data loss and irregularities. An inefficient queuing system causes conflicts between customers and the laundry. Therefore, to handle this problem you can use the management information system at Hade Laundry. This system is designed using the waterfall method. Customer queue data collection uses the FIFO (First-In, First-Out) algorithm to maintain queue stability or sequence. The programming language used in designing this system is PHP and the CodeIgniter framework, and uses a MySQL database. The results of the research are a website-based management information system with the application of the FIFO algorithm. The implementation of this algorithm is able to manage customer queues well (organized and structured), so as to minimize the occurrence of conflicts between customers and laundry parties.